QUALITY OF TIFTON AND ALFALFA HAYS AND EQUINE BODY BIOMETRICS - Oliveira, Katia de [UNESP]; Tsuzukibashi, Denise [UNESP]; Fachiolli, Daniele Floriano [UNESP]; Watanabe, Marcos Jun [UNESP]; Vera, Joao Henrique Silva [UNESP]; Silva Barros, Juliana da [UNESP]; Costa, Ciniro [UNESP] (Inst Zootecnia, 2023)
This paper targets the quality of tifton bermudagrass (Cynodon spp.) and alfalfa (Medicago sativa) hays in isoproteic and isoenergetic diets on horse body biometrics. Six equines, between 6.5 +/- 0.5 years old and with an mean body weight of 354 +/- 50kg, were used in this study. The treatments consisted of six diets and the experimental delineation was the Latin square (6x6). The diet's forage was composed by a combination of hays, in a factorial scheme (2x3), with two forages (tifton bermudagrass and alfalfa) and three types of hay (A, B and C). There was a significant effect in the variables body weight, abdominal girth, fecal water content, and fecal production for the forage type. Greater digestibility coefficient of dietary dry matter values were identified in the diets composed by type A and B alfalfa hay (64.71 +/- 2.38% and 63.45 +/- 2.41%, respectively), that have significantly surpassed (P = 0.0061) the results obtained for the type C hay diets. It was possible to conclude that the alfalfa hay provided a reduction in the horse's body weight and thoracic perimeter, what can be explained by the greater verified digestibility, as well as the lesser fecal water retention with the diets containing only the legume.
Keywords: Abdominal Girth; Body Weight; Digestibility; Forage; Horse